Analisis Sentimen Pengguna Aplikasi SIMANTAP Pondok Pesantren Salafiyah Syafi’iyah Situbondo - Ach. Zubairi; Luckman Ashary (Jurnal Multidisiplin Ibrahimy, 2023)
Pondok Pesantren Salafiyah Syafi'iyah Sukorejo Situbondo provides a payment application called SIMANTAP. This application aims to make it easier for guardians of students to make payments for bills given by Islamic boarding schools. Along the way, some obstacles arise; users tend to give their views in a comment. These comments will later provide an overview of the user's response to the SIMANTAP application. This study will analyze comment data using the Naïve Bayes Classifier. The data was taken from September 2021 to October 2021. As a result, users tend to give a positive response of 89%. Based on the test data results using the Naïve Bayes classifier algorithm, the classification can predict quite well; this is shown by the precision results of 82%, 97% recall, and 89% fi-score.